2020
DOI: 10.2166/wst.2020.332
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked-substituted (esterified/etherified) starch derivatives as aqueous heavy metal ion adsorbent: a review

Abstract: Starch is a biopolymer with outstanding economic and environmental friendly attributes which has driven technological innovations to enhance its applications in food and nonfood industries. Starch is constituted by O-H groups with valency and electronic characteristics that can initiate adsorption of aqueous heavy metal ions (AHMIs). However, this can be enhanced using various modification sequences. A common procedure is the cross-linking and substitution of the O-H groups via esterification and/or etherifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…This may be due to the fact that starch was hydrolyzed by NaOH, which changed the morphology of the starch and produced more available functional groups. 43 The surface of the SPR was smooth and had fewer voids. After modification, the material appeared corrugated, wrinkled, and loose, forming an irregular layered shape and a microporous structure that might help create more adsorption sites for Cd 2+ binding.…”
Section: Resultsmentioning
confidence: 98%
“…This may be due to the fact that starch was hydrolyzed by NaOH, which changed the morphology of the starch and produced more available functional groups. 43 The surface of the SPR was smooth and had fewer voids. After modification, the material appeared corrugated, wrinkled, and loose, forming an irregular layered shape and a microporous structure that might help create more adsorption sites for Cd 2+ binding.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of JRDF-EAG, the peaks at 1742 cm −1 (corresponding to asymmetric bending of the acetyl group) and 1100 cm −1 (representing the stretching vibration of C–O–C) transferred to 1752 and 1085 cm −1 , respectively; and the peak at 1525 cm −1 (indicative of the stretching vibration of –C=O) transferred to 1519 cm −1 , evidencing the introduction of the propenyl ester group [ 19 ]. Moreover, a new peak at around 2395 cm −1 (corresponding to the stretching vibration of the phosphate group) appeared in the spectrum of JRDF-EPG [ 10 , 30 ], demonstrating that the phosphate group had been grafted with JRDF. Similar results were obtained by Djordjević et al [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the peaks at wavenumbers of 1,632 and 1,110, 1,378 cm −1 (separately indicative of the asymmetric bend of acetyl group, C-H, and -C=O, respectively, Gil-López et al, 2019) in the spectrum of JKF separately presented at wavenumbers of 1,622, 1,107, and 1,369 cm −1 in the spectrum of JKE-SGEA, demonstrating that acyl ester groups have been introduced into JKF molecules after acetylation. Additionally, compared with the spectrum of JKF, the spectrum of JKF-SGEH has two new peaks appearing at wavenumber of 913 and 2,734 cm −1 (indicative of the stretching and flexion of C-O and C-H, respectively), and the peak at 2850 cm −1 transferred to 2,845 cm −1 (indicative of the flexion of C-H), which is attributed to the introduction of hydroxypropyl group after hydroxypropylation (Tapia-Hernández et al, 2019b;Akinterinwa et al, 2020). Previous studies shown that superfine-grinding, acetylation and hydroxypropylation all could influence the structure of fibers via changing their chemical bonds (Shaikh et al, 2019;Zheng et al, 2022).…”
Section: Ft-irmentioning
confidence: 99%